Preparation method of novel explosive special for composite metal
By using porous granular ammonium nitrate and diesel in the new composite metal special explosives, and adding stable modifiers and regulators, the interface properties and performance of nanomaterials are optimized, the poor performance and insufficient stability of existing explosives are solved. The problem of this problem achieves more efficient explosion performance and heat resistance.
Patent Information
- Application Number
- CN202411309045.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-07
AI Technical Summary
The explosives for existing new composite metals have poor explosive performance, are prone to dehydration and have poor heat resistance and stability, which affects their use efficiency.
The interfacial and performance stability of explosives are optimized through the coordination and coordination of nano-bentonite, carbon nanotubes, nanosilicon sols and other materials. Improve explosion performance and heat resistance.
It significantly improves the explosive performance and heat resistance of explosives, ensures stable performance in humid environments and high temperature conditions, and improves the use efficiency.
Smart Images

Figure BDA0005050117570000111 
Figure BDA0005050117570000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of explosives, and in particular to a method for preparing a novel composite metal special explosive. Background Art
[0002] Explosive welding is a solid phase welding method, usually used for welding dissimilar metals. Modern industry requires a variety of metal composite materials, such as titanium steel and carbon steel, stainless steel and carbon steel welded composite plates, etc., and welding of metal materials with different chemical compositions and physical properties such as titanium, copper, aluminum, and steel; existing new composite metal-specific explosives usually use modified ammonium oil or powdered (emulsified) explosives as the base explosives, and add other substances to mix them. However, the existing technology has the following problems: the products used have poor explosive performance, are easy to deliquesce, and have poor heat resistance and stability, which affects the use efficiency of the products. Based on this, the present invention further improves and processes them. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing a novel composite metal special explosive to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a method for preparing a novel composite metal special explosive, comprising the following steps:
[0006] Step 1: Mix 90-95 parts of porous granular ammonium nitrate and 4-7 parts of diesel at room temperature for 20 minutes to obtain porous granular ammonium nitrate oil explosive;
[0007] Step 2: Stir and mix 2 to 5 parts of a stabilizing modifier and 0.5 to 2.5 parts of a regulator, then add them into the porous granular ammonium nitrate oil explosive and continue stirring for 2 to 5 minutes at a stirring speed of 150 to 200 r / min. After stirring, the novel composite metal special explosive of the present invention is obtained.
[0008] Preferably, the preparation method of the stabilizing modifier is:
[0009] S01: calcining the nano-bentonite for thermal improvement;
[0010] S011: The nano-bentonite is heated to 165-175°C at a rate of 2-5°C / min, kept at this temperature for 5-10 minutes, then heated to 275°C at a rate of 1-3°C / min, kept at this temperature for 2-5 minutes, and finally air-cooled to 55°C;
[0011] S012: mixing the above-treated nano-bentonite, yttrium nitrate solution and nano-boron nitride in a weight ratio of 5:3:1, and after the stirring is completed, filtering and drying to obtain heat-modified nano-bentonite;
[0012] S02: placing the heat-modified nano-bentonite in a sufficient amount of dopamine hydrochloride solution and dispersing it evenly to obtain a nano-bentonite liquid;
[0013] S03: The nano-bentonite liquid and the modifier are mixed in a weight ratio of 4:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a stable modifier.
[0014] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 4-6%.
[0015] Preferably, the stirring speed of the mixing and stirring treatment is 500-600 r / min, and the stirring is for 1 hour.
[0016] Preferably, the preparation method of the modifier is:
[0017] The carbon nanotubes are first irradiated in a proton irradiation box for 5 to 10 minutes with an irradiation power of 350 to 400 W. After the irradiation, 2 to 5 parts of the irradiated carbon nanotubes, 1 to 3 parts of nano-silica sol, 4 to 7 parts of lanthanum chloride solution, 2 to 3 parts of carboxymethyl cellulose and 1 to 3 parts of nano-silicon dioxide are fully blended and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier.
[0018] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%.
[0019] Preferably, the blending ball mill has a rotation speed of 750 to 850 r / min and the ball milling is performed for 20 to 30 minutes.
[0020] Preferably, the preparation method of the regulator is:
[0021] S11: mixing the nanocarbon fiber, the silane coupling agent and the sodium lignin sulfonate solution in a weight ratio of 4:1:7 to obtain a nanocarbon fiber liquid;
[0022] S12: mixing flaky talc in a sufficient amount of potassium permanganate solution, then washing and drying, and mixing 2 to 5 parts of the dried flaky talc, 1 to 3 parts of urea and 2 to 4 parts of 5% by mass sodium alginate solution to obtain a flaky talc agent;
[0023] S13: Mix the nanocarbon fiber liquid and the flaky talc powder in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water, and dry to obtain a regulator.
[0024] Preferably, the silane coupling agent is silane coupling agent KH550; and the mass fraction of the sodium lignin sulfonate solution is 4-6%.
[0025] Preferably, the mass fraction of the potassium permanganate solution is 2-5%.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The porous granular ammonium oil explosive used in the invention is combined with a stabilizing modifier and a regulator as functional additives, and the two are coordinated and synergistic, so that the explosive performance effect of the product is remarkable, and the product is easy to deliquesce and has excellent heat-resistant stability effects; the stabilizing modifier adopts nano-bentonite, which is heated to 165-175°C at a rate of 2-5°C / min, kept warm for 5-10 minutes, then heated to 275°C at a rate of 1-3°C / min, kept warm for 2-5 minutes, and finally air-cooled to 55°C, and a step-by-step thermal improvement is adopted to optimize the active efficiency and interlayer spacing of the nano-bentonite, thereby improving the distribution effect of the nano-bentonite in the system and improving the interface of the product, and at the same time, yttrium nitrate solution and nano-boron nitride are used for blending and coordination to enhance the performance stability of the product system, and at the same time, dopamine hydrochloride solution is used for blending and coordination to facilitate better blending and coordination of the product raw materials with the modifier, and the modifier adopts carbon nanotubes for irradiation in a proton irradiation box before irradiation to stimulate the active efficiency of the carbon nanotubes, and at the same time, the carbon nanotubes The wall surface area is high, and the nano-silica sol, lanthanum chloride solution, carboxymethyl cellulose and nano-silicon dioxide are coordinated and ball-milled. Through the coordination between the raw materials, the coordination effect of the modifier and the nano-bentonite liquid is enhanced, so that the interface of the product raw materials can be better combined, and the system performance stability is enhanced, the explosion performance of the product is better improved, and the deliquescent and heat-resistant stability effects are remarkable; the regulator adopts nano-carbon fiber to be coordinated and coordinated with a silane coupling agent and a sodium lignin sulfonate solution, so as to better improve the dispersibility and interface of the raw materials, and then the flaky talcum powder can be adjusted and improved. The flaky talcum powder adopts flaky talcum powder to be treated with a potassium permanganate solution to optimize its active efficiency, and then mixed with urea and a sodium alginate solution with a mass fraction of 5%, and the system performance is strengthened by the flake structure of the flaky talcum powder and the needle structure of the carbon fiber, so that the regulator is better coordinated and synergistic with the stable modifier, so that the performance of the product is further improved. DETAILED DESCRIPTION
[0028] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The preparation method of a novel composite metal special explosive of the present embodiment comprises the following steps:
[0030] Step 1: Mix 90-95 parts of porous granular ammonium nitrate and 4-7 parts of diesel at room temperature for 20 minutes to obtain porous granular ammonium nitrate oil explosive;
[0031] Step 2: Stir and mix 2 to 5 parts of a stabilizing modifier and 0.5 to 2.5 parts of a regulator, then add them into the porous granular ammonium nitrate oil explosive and continue stirring for 2 to 5 minutes at a stirring speed of 150 to 200 r / min. After stirring, the novel composite metal special explosive of the present invention is obtained.
[0032] The preparation method of the stable modifier of this embodiment is:
[0033] S01: calcining the nano-bentonite for thermal improvement;
[0034] S011: The nano-bentonite is heated to 165-175°C at a rate of 2-5°C / min, kept at this temperature for 5-10 minutes, then heated to 275°C at a rate of 1-3°C / min, kept at this temperature for 2-5 minutes, and finally air-cooled to 55°C;
[0035] S012: mixing the above-treated nano-bentonite, yttrium nitrate solution and nano-boron nitride in a weight ratio of 5:3:1, and after the stirring is completed, filtering and drying to obtain heat-modified nano-bentonite;
[0036] S02: placing the heat-modified nano-bentonite in a sufficient amount of dopamine hydrochloride solution and dispersing it evenly to obtain a nano-bentonite liquid;
[0037] S03: The nano-bentonite liquid and the modifier are mixed in a weight ratio of 4:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a stable modifier.
[0038] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the dopamine hydrochloride solution is 4-6%.
[0039] The stirring speed of the mixing and stirring process in this embodiment is 500-600 r / min, and the stirring is for 1 hour.
[0040] The preparation method of the modifier of this embodiment is:
[0041] The carbon nanotubes are first irradiated in a proton irradiation box for 5 to 10 minutes with an irradiation power of 350 to 400 W. After the irradiation, 2 to 5 parts of the irradiated carbon nanotubes, 1 to 3 parts of nano-silica sol, 4 to 7 parts of lanthanum chloride solution, 2 to 3 parts of carboxymethyl cellulose and 1 to 3 parts of nano-silicon dioxide are fully blended and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier.
[0042] The mass fraction of the lanthanum chloride solution in this embodiment is 2-5%.
[0043] The blending ball mill of this embodiment has a full rotation speed of 750 to 850 r / min, and the ball milling takes 20 to 30 minutes.
[0044] The preparation method of the regulator of this embodiment is:
[0045] S11: mixing the nanocarbon fiber, the silane coupling agent and the sodium lignin sulfonate solution in a weight ratio of 4:1:7 to obtain a nanocarbon fiber liquid;
[0046] S12: mixing flaky talc in a sufficient amount of potassium permanganate solution, then washing and drying, and mixing 2 to 5 parts of the dried flaky talc, 1 to 3 parts of urea and 2 to 4 parts of 5% by mass sodium alginate solution to obtain a flaky talc agent;
[0047] S13: Mix the nanocarbon fiber liquid and the flaky talc powder in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water, and dry to obtain a regulator.
[0048] The silane coupling agent in this embodiment is silane coupling agent KH550; the mass fraction of the sodium lignin sulfonate solution is 4-6%.
[0049] The mass fraction of the potassium permanganate solution in this embodiment is 2-5%.
[0050] Example 1.
[0051] The preparation method of a novel composite metal special explosive of this embodiment comprises the following steps:
[0052] Step 1: Mix 90 parts of porous granular ammonium nitrate and 4 parts of diesel at room temperature for 20 minutes to obtain porous granular ammonium nitrate oil explosive;
[0053] Step 2: Stir and mix 2 parts of a stabilizing modifier and 0.5 parts of a regulator thoroughly, then add them into the porous granular ammonium nitrate oil explosive and continue stirring for 2 minutes at a stirring speed of 150 r / min. After stirring, the novel composite metal special explosive of the present invention is obtained.
[0054] The preparation method of the stable modifier of this embodiment is:
[0055] S01: calcining the nano-bentonite for thermal improvement;
[0056] S011: Nano-bentonite was heated to 165°C at a rate of 2°C / min, kept at that temperature for 5 min, then heated to 275°C at a rate of 1°C / min, kept at that temperature for 2 min, and finally air-cooled to 55°C;
[0057] S012: mixing the above-treated nano-bentonite, yttrium nitrate solution and nano-boron nitride in a weight ratio of 5:3:1, and after the stirring is completed, filtering and drying to obtain heat-modified nano-bentonite;
[0058] S02: placing the heat-modified nano-bentonite in a sufficient amount of dopamine hydrochloride solution and dispersing it evenly to obtain a nano-bentonite liquid;
[0059] S03: The nano-bentonite liquid and the modifier are mixed in a weight ratio of 4:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a stable modifier.
[0060] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 4%.
[0061] The stirring speed of the mixing and stirring process in this embodiment is 500 r / min, and the stirring is for 1 hour.
[0062] The preparation method of the modifier of this embodiment is:
[0063] The carbon nanotubes were first irradiated in a proton irradiation box for 5 minutes with an irradiation power of 350W. After the irradiation, 2 parts of irradiated carbon nanotubes, 1 part of nano-silica sol, 4 parts of lanthanum chloride solution, 2 parts of carboxymethyl cellulose and 1 part of nano-silica were fully blended and ball-milled. After the ball-milling was completed, the mixture was washed with water and dried to obtain a modifier.
[0064] The mass fraction of the lanthanum chloride solution in this embodiment is 2%.
[0065] The blending ball milling speed of this embodiment is 750r / min, and the ball milling is 20min.
[0066] The preparation method of the regulator of this embodiment is:
[0067] S11: mixing the nanocarbon fiber, the silane coupling agent and the sodium lignin sulfonate solution in a weight ratio of 4:1:7 to obtain a nanocarbon fiber liquid;
[0068] S12: mixing flaky talc in a sufficient amount of potassium permanganate solution, then washing and drying, and mixing 2 parts of the dried flaky talc, 1 part of urea and 2 parts of 5% by mass sodium alginate solution to obtain a flaky talc agent;
[0069] S13: The nanocarbon fiber liquid and the flaky talc powder are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a regulator.
[0070] The silane coupling agent in this embodiment is silane coupling agent KH550; the mass fraction of the sodium lignin sulfonate solution is 4%.
[0071] The mass fraction of the potassium permanganate solution in this embodiment is 2%.
[0072] Example 2.
[0073] The preparation method of a novel composite metal special explosive of this embodiment comprises the following steps:
[0074] Step 1: Mix 95 parts of porous granular ammonium nitrate and 7 parts of diesel at room temperature for 20 minutes to obtain porous granular ammonium nitrate oil explosive;
[0075] Step 2: Stir and mix 5 parts of a stabilizing modifier and 2.5 parts of a regulating agent thoroughly, then add them into the porous granular ammonium nitrate oil explosive and continue stirring for 5 minutes at a stirring speed of 200 r / min. After stirring, the novel composite metal special explosive of the present invention is obtained.
[0076] The preparation method of the stable modifier of this embodiment is:
[0077] S01: calcining the nano-bentonite for thermal improvement;
[0078] S011: Nano-bentonite was heated to 175°C at a rate of 5°C / min, kept at that temperature for 10 min, then heated to 275°C at a rate of 3°C / min, kept at that temperature for 5 min, and finally air-cooled to 55°C;
[0079] S012: mixing the above-treated nano-bentonite, yttrium nitrate solution and nano-boron nitride in a weight ratio of 5:3:1, and after the stirring is completed, filtering and drying to obtain heat-modified nano-bentonite;
[0080] S02: placing the heat-modified nano-bentonite in a sufficient amount of dopamine hydrochloride solution and dispersing it evenly to obtain a nano-bentonite liquid;
[0081] S03: The nano-bentonite liquid and the modifier are mixed in a weight ratio of 4:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a stable modifier.
[0082] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 6%.
[0083] The stirring speed of the mixing and stirring process in this embodiment is 600 r / min, and the stirring is for 1 hour.
[0084] The preparation method of the modifier of this embodiment is:
[0085] The carbon nanotubes were first irradiated in a proton irradiation box for 10 minutes with an irradiation power of 400 W. After the irradiation, 5 parts of irradiated carbon nanotubes, 3 parts of nano-silica sol, 7 parts of lanthanum chloride solution, 3 parts of carboxymethyl cellulose and 3 parts of nano-silica were fully blended and ball-milled. After the ball-milling was completed, the mixture was washed with water and dried to obtain a modifier.
[0086] The mass fraction of the lanthanum chloride solution in this embodiment is 5%.
[0087] The blending ball milling speed of this embodiment is 850r / min, and the ball milling is 30min.
[0088] The preparation method of the regulator of this embodiment is:
[0089] S11: mixing the nanocarbon fiber, the silane coupling agent and the sodium lignin sulfonate solution in a weight ratio of 4:1:7 to obtain a nanocarbon fiber liquid;
[0090] S12: mixing flaky talc in a sufficient amount of potassium permanganate solution, then washing and drying, and mixing 5 parts of the dried flaky talc, 3 parts of urea and 4 parts of 5% by mass sodium alginate solution to obtain a flaky talc agent;
[0091] S13: The nanocarbon fiber liquid and the flaky talc powder are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a regulator.
[0092] The silane coupling agent in this embodiment is silane coupling agent KH550; the mass fraction of the sodium lignin sulfonate solution is 6%.
[0093] The mass fraction of the potassium permanganate solution in this embodiment is 5%.
[0094] Example 3.
[0095] The preparation method of a novel composite metal special explosive of the present embodiment comprises the following steps:
[0096] Step 1: 92.5 parts of porous granular ammonium nitrate and 5.5 parts of diesel are mixed at room temperature for 20 minutes to obtain porous granular ammonium nitrate oil explosive;
[0097] Step 2: Stir and mix 3.5 parts of a stabilizing modifier and 2.0 parts of a regulator thoroughly, then add them into the porous granular ammonium nitrate oil explosive and continue stirring for 3.5 minutes at a stirring speed of 170 r / min. After stirring, the novel composite metal special explosive of the present invention is obtained.
[0098] The preparation method of the stable modifier of this embodiment is:
[0099] S01: calcining the nano-bentonite for thermal improvement;
[0100] S011: Nano-bentonite was heated to 170°C at a rate of 3.5°C / min, kept at this temperature for 7.5 min, then heated to 275°C at a rate of 2°C / min, kept at this temperature for 3.5 min, and finally air-cooled to 55°C;
[0101] S012: mixing the above-treated nano-bentonite, yttrium nitrate solution and nano-boron nitride in a weight ratio of 5:3:1, and after the stirring is completed, filtering and drying to obtain heat-modified nano-bentonite;
[0102] S02: placing the heat-modified nano-bentonite in a sufficient amount of dopamine hydrochloride solution and dispersing it evenly to obtain a nano-bentonite liquid;
[0103] S03: The nano-bentonite liquid and the modifier are mixed in a weight ratio of 4:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a stable modifier.
[0104] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the dopamine hydrochloride solution is 5%.
[0105] The stirring speed of the mixing and stirring process in this embodiment is 550 r / min, and the stirring is for 1 hour.
[0106] The preparation method of the modifier of this embodiment is:
[0107] The carbon nanotubes were first irradiated in a proton irradiation box for 7.5 minutes at an irradiation power of 375 W. After the irradiation was completed, 3.5 parts of the irradiated carbon nanotubes, 2 parts of nano-silica sol, 5.5 parts of lanthanum chloride solution, 2.5 parts of carboxymethyl cellulose and 2 parts of nano-silica were fully blended and ball-milled. After the ball-milling was completed, the mixture was washed with water and dried to obtain a modifier.
[0108] The mass fraction of the lanthanum chloride solution in this embodiment is 3.5%.
[0109] The blending ball milling speed of this embodiment is 800r / min, and the ball milling time is 25min.
[0110] The preparation method of the regulator of this embodiment is:
[0111] S11: mixing the nanocarbon fiber, the silane coupling agent and the sodium lignin sulfonate solution in a weight ratio of 4:1:7 to obtain a nanocarbon fiber liquid;
[0112] S12: mixing the flaky talc powder in a sufficient amount of potassium permanganate solution, then washing and drying, and mixing 3.5 parts of the dried flaky talc powder, 2 parts of urea and 3 parts of 5% by mass sodium alginate solution to obtain a flaky talc powder;
[0113] S13: Mix the nanocarbon fiber liquid and the flaky talc powder in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1250 r / min for 1 h. After the ball milling is completed, wash with water, and dry to obtain a regulator.
[0114] The silane coupling agent in this embodiment is silane coupling agent KH550; the mass fraction of the sodium lignin sulfonate solution is 5%.
[0115] The mass fraction of the potassium permanganate solution in this embodiment is 3.5%.
[0116] Comparative Example 1.
[0117] The difference from Example 3 is that no stabilizing modifier is added.
[0118] Comparative Example 2.
[0119] The difference from Example 3 is that S01 treatment was not used in the preparation of the stabilizing modifier.
[0120] Comparative Example 3.
[0121] The difference from Example 3 is that step S011 is not used in the S01 treatment.
[0122] Comparative Example 4.
[0123] The difference from Example 3 is that step S012 is not used in the S01 treatment.
[0124] Comparative Example 5.
[0125] The difference from Example 3 is that no modifier treatment is used in the preparation of the stabilizing modifier.
[0126] Comparative Example 6.
[0127] The difference from Example 3 is that no regulator was added.
[0128] Comparative Example 7.
[0129] The difference from Example 3 is that no nano carbon fiber liquid is added to the regulator.
[0130] Comparative Example 8.
[0131] The difference from Example 3 is that no flaky talc is added to the conditioning agent.
[0132] Comparative Example 9.
[0133] The difference from Example 3 is that the flaky talc agent is replaced by flaky talc powder.
[0134] The products of Examples 1-3 and Comparative Examples 1-9 were placed under normal conditions, and placed in a 5% humidity environment for 48 hours to test moisture resistance stability, and placed at 75°C for 48 hours to test heat resistance. The performance measurement results are as follows
[0135]
[0136] It can be concluded from Examples 1-3 and Comparative Examples 1-9 that
[0137] The product of Example 3 of the present invention has excellent detonation velocity and violentness under normal conditions, and the product has remarkable moisture and heat resistance stability effects;
[0138] From Comparative Examples 1-9 and Example 3, it can be seen that the performance of the product without adding a stabilizing modifier or a regulating agent has a significant deterioration trend. The coordinated combination of the two can achieve a coordinated improvement.
[0139] When S01 treatment is not used in the preparation of the stabilizing modifier, S011 step is not used in the S01 treatment, S012 step is not used in the S01 treatment, and modifier treatment is not used in the preparation of the stabilizing modifier, the performance of the product tends to deteriorate. When the specific S01 treatment of the present invention is used in combination with the modifier treatment of the present invention, the performance effect of the product is most significant. When no modifier treatment is used, the performance of the product tends to deteriorate significantly in the preparation of the stabilizing modifier.
[0140] When no nano carbon fiber liquid is added to the regulator, no flaky talcum powder is added to the regulator, and the flaky talcum powder is replaced by flaky talcum powder, the performance of the product also shows a trend of deterioration. The performance effect of the product is most significant when the specific flaky talc agent of the present invention is combined with the nano carbon fiber liquid of the present invention.
[0141] Since the modifier has a significant impact on the performance of the product, further research is needed:
[0142] The preparation method of the modifier is:
[0143] The carbon nanotubes were first irradiated in a proton irradiation box for 7.5 minutes at an irradiation power of 375 W. After the irradiation was completed, 3.5 parts of the irradiated carbon nanotubes, 2 parts of nano-silica sol, 5.5 parts of lanthanum chloride solution, 2.5 parts of carboxymethyl cellulose and 2 parts of nano-silica were fully blended and ball-milled. After the ball-milling was completed, the mixture was washed with water and dried to obtain a modifier.
[0144] Experimental example 1.
[0145] The only difference from Example 3 is that no irradiated carbon nanotubes are added in the preparation of the modifier.
[0146] Experimental example 2.
[0147] The only difference from Example 3 is that no nano-silicon dioxide is added in the preparation of the modifier.
[0148] Experimental Example 3.
[0149] The only difference from Example 3 is that nano silica sol and carboxymethyl cellulose are not added in the preparation of the modifier.
[0150] Experimental Example 4.
[0151] The only difference from Example 3 is that the lanthanum chloride solution is replaced by deionized water.
[0152]
[0153] It can be seen from Experimental Examples 1-4 that irradiated carbon nanotubes were not added in the preparation of the modifier. Among the preparation factors of the modifier, the performance of the product deteriorated significantly, followed by the absence of nano-silicon dioxide. At the same time, nano-silica sol and carboxymethyl cellulose were not added in the preparation of the modifier, and deionized water was used instead of lanthanum chloride solution. The performance of the product tended to deteriorate. Only by using the specific raw materials of the present invention, the performance effect of the product is the most significant. Using other raw materials instead cannot achieve the technical effect of the present invention.
[0154] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0155] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a novel composite metal special explosive, characterized in that: The following steps are involved: Step 1: Mix 90-95 parts of porous granular ammonium nitrate and 4-7 parts of diesel at room temperature for 20 minutes to obtain porous granular ammonium nitrate oil explosive; Step 2: Stir and mix 2 to 5 parts of a stabilizing modifier and 0.5 to 2.5 parts of a regulator, then add them into the porous granular ammonium nitrate oil explosive and continue stirring for 2 to 5 minutes at a stirring speed of 150 to 200 r / min. After stirring, the novel composite metal special explosive of the present invention is obtained.
2. The method for preparing a novel composite metal special explosive according to claim 1, characterized in that: The preparation method of the stable modifier is: S01: calcining the nano-bentonite for thermal improvement; S011: The nano-bentonite is heated to 165-175°C at a rate of 2-5°C / min, kept at this temperature for 5-10 minutes, then heated to 275°C at a rate of 1-3°C / min, kept at this temperature for 2-5 minutes, and finally air-cooled to 55°C; S012: mixing the above-treated nano-bentonite, yttrium nitrate solution and nano-boron nitride in a weight ratio of 5:3:1, and after the stirring is completed, filtering and drying to obtain heat-modified nano-bentonite; S02: placing the heat-modified nano-bentonite in a sufficient amount of dopamine hydrochloride solution and dispersing it evenly to obtain a nano-bentonite liquid; S03: The nano-bentonite liquid and the modifier are mixed in a weight ratio of 4:3 and ball-milled at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a stable modifier.
3. The method for preparing a novel composite metal special explosive according to claim 2, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 4-6%.
4. The method for preparing a novel composite metal special explosive according to claim 2, characterized in that: The stirring speed of the mixing and stirring treatment is 500-600 r / min, and the stirring is for 1 hour.
5. The method for preparing a novel composite metal special explosive according to claim 2, characterized in that: The preparation method of the modifier is: The carbon nanotubes are first irradiated in a proton irradiation box for 5 to 10 minutes with an irradiation power of 350 to 400 W. After the irradiation, 2 to 5 parts of the irradiated carbon nanotubes, 1 to 3 parts of nano-silica sol, 4 to 7 parts of lanthanum chloride solution, 2 to 3 parts of carboxymethyl cellulose and 1 to 3 parts of nano-silicon dioxide are fully blended and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier.
6. The method for preparing a novel composite metal special explosive according to claim 5, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%.
7. The method for preparing a novel composite metal special explosive according to claim 5, characterized in that: The blending ball mill has a full rotation speed of 750 to 850 r / min and the ball mill is performed for 20 to 30 minutes.
8. The method for preparing a novel composite metal special explosive according to claim 1, characterized in that: The preparation method of the regulator is: S11: mixing the nanocarbon fiber, the silane coupling agent and the sodium lignin sulfonate solution in a weight ratio of 4:1:7 to obtain a nanocarbon fiber liquid; S12: mixing flaky talc in a sufficient amount of potassium permanganate solution, then washing and drying, and mixing 2 to 5 parts of the dried flaky talc, 1 to 3 parts of urea and 2 to 4 parts of 5% by mass sodium alginate solution to obtain a flaky talc agent; S13: Mix the nanocarbon fiber liquid and the flaky talc powder in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water, and dry to obtain a regulator.
9. The method for preparing a novel composite metal special explosive according to claim 8, characterized in that: The silane coupling agent is silane coupling agent KH550; the mass fraction of the sodium lignin sulfonate solution is 4-6%.
10. The method for preparing a novel composite metal special explosive according to claim 8, characterized in that: The mass fraction of the potassium permanganate solution is 2-5%.